Inter-jurisdictional cooperation on pharmaceutical product listing agreements: views from Canadian provinces - Morgan Steven G; Thomson Paige A; Daw Jamie R; Friesen Melissa K (BMC, 2013)
Abstract Background Confidential product listing agreements (PLAs) negotiated between pharmaceutical manufacturers and individual health care payers may contribute to unwanted price disparities, high administrative costs, and unequal bargaining power within and across jurisdictions. In the context of Canada's decentralized health system, we aimed to document provincial policy makers' perceptions about collaborative PLA negotiations. Methods We conducted semi-structured telephone interviews with a senior policy maker from nine of the ten Canadian provinces. We conducted a thematic analysis of interview transcripts to identify benefits, drawbacks, and barriers to routine collaboration on PLA negotiations. Results Canadian policy makers expressed support for joint negotiations of PLAs in principle, citing benefits of increased bargaining power and reduced inter-jurisdictional inequities in drug prices and formulary listings. However, established policy institutions and the politics of individual jurisdictional authority are formidable barriers to routine PLA collaboration. Achieving commitment to a joint process may be difficult to sustain among heterogeneous and autonomous partners. Conclusions Though collaboration on PLA negotiation is an extension of collaboration on health technology assessment, it is a very significant next step that requires harmonization of the outcomes of decision-making processes. Views of policy makers in Canada suggest that sustaining routine collaborations on PLA negotiations may be difficult unless participating jurisdictions have similar policy institutions, capacities to implement coverage decisions, and local political priorities.